The Idea of Linguistic Unity Reflected in the Philological Conception of Aron Pumnul - Vranceanu, Felicia (My University, 2019)
Through his entire activity, Aron Pumnus has become a true symbol of Romanianism in Bucovina. Encyclopedic personality, manifested in various fields (linguistics, literary history, philosophy, history, journalism, etc.), the Romanian scholar contributes decisively to the promotion of national values. The journalistic activity of the great Romanian scholar is subordinated to these principles, giving us a detailed picture of the opinions on the past, present and future of the Romanian language as a defining component of the national ideal. The linguistic conception of Aron Pumnus, ironized and criticized many times, reflects the aspirations of a generation that will definitely contribute to the achievement of a unitary Romanian language. There are eloquent studies such as “Neatîrnarea limbei romînesci în desvoltarea sa și în modul de a o scrie”, “Literele corespunzătoare firei limbei romînesci și modul de a scrie cu ele”, “Binescriința limbei românesci cu litere romane”, which eloquently illustrate the idea supported by this “apostle of Romanianism”: “The nation is the contents of a people of the same blood, who speak the same language and have the same tradition. The people are the body of the nation, the tongue is its soul.”
Keywords: romanian language, linguistic unity, linguistic conception, literary history, etymology